Strategi Pengelolaan Keuangan Bagi Mahasiswa Penerima Kip Kuliah Di Perguruan Tinggi - Antonius Nggangga; Debi A. D. Mauwalan; Aletha Maria Nenabu (GLOBAL SCIENTS PUBLISHER, 2026)
This community service aims to provide financial management assistance to college students who receive the Kartu Indonesia Pintar (KIP) Kuliah. Many recipient students face difficulties in managing their living allowance, often leading to deficits before the end of the semester. The method used in this activity consists of financial literacy socialization, budgeting simulations using the 50/30/20 method, and evaluation through pre-test and post-test. The result of this program shows a significant increase in students' financial intelligence and budgeting skills. In conclusion, structured financial literacy assistance is highly effective in helping KIP Kuliah recipients optimize their funds for academic and basic living needs.